Earthquakes and project management utilization: a case of recent earthquakes of Iran - Tabassi, Amin Akhavan; A.H., Abu Bakar (2008)
Iran is located in a very complex tectonic environment; it has experienced more than 25 strong earthquakes with a magnitude of 6 or more in this century. The huge earthquakes in the century have killed more than 170,000 lives, destroyed many towns and thousands of villages, and caused extensive economic damage. The research contrasts the fatalities and destruction of some of the greatest earthquakes of Iran and other countries from 1950. The results show the deaths and disasters of earthquakes in Iran are 23 times more than the theoretical expectation. On the other hand, comparison of recent records on the impact of earthquake hazards of similar magnitude in countries of varying levels of development and Iran make an astonishing result. Comparing California’s damages to construction after the past earthquakes with Iran’s disasters of earthquakes in same magnitude suggests that poor construction practice and lack of effective project management utilization played major roles in the vast destruction and high death toll and sorrowful tragedies within the cities of Iran. Despite the history of tragic earthquakes, and their continuing recurrence in Iran the study aims to make the government, companies and managers of disasters aware of the aftermath in different parts of Iran of low quality construction and lack of project management knowledge utilization; and make a consciousness for applying proper ways to prevent probable damages in future.